If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10v + 23 = 93 Reorder the terms: 23 + 10v = 93 Solving 23 + 10v = 93 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 10v = 93 + -23 Combine like terms: 23 + -23 = 0 0 + 10v = 93 + -23 10v = 93 + -23 Combine like terms: 93 + -23 = 70 10v = 70 Divide each side by '10'. v = 7 Simplifying v = 7
| 2x^2+64x+512=0 | | 7(d-5)+6= | | 2x^2+512=0 | | 3x-y(x+10)=9 | | z^2+2(1-i)z+2i=0 | | =1+3x | | x-6.1=5.3 | | 3x^5-14x^3-5x=0 | | -5k+2.7+2.4k+2.1k-5= | | 7x+4=19+2x | | h=24 | | 4x-(5x+5)=5x-47 | | y+1=-y+3 | | 3+5x=8+2x | | (x-y)*(4x-2y)= | | f(-x)=x^2-8x+9 | | 8x/3-3=29 | | (12x+3)+(-7x+5)= | | -2y-2.4+1.1-0.8y+2= | | w=-8/-7 | | -3(2n-3)=-4n+45 | | 5t-2(5+4t)=3+1t+-8 | | 5t+-2(5+4t)=3+1t+-8 | | 2x+3*6=36 | | 11x-9x+3=21 | | 704=(x^3)+(3x^2) | | -7w=-8 | | -4+2(n-3)=22 | | 6x+4=-3x+14 | | 14-2x+5x=4(-2x-5)-6 | | 3*10=10+5s | | 2z+-5+-10=-8+-2z |